Biogeography and climate change threats of supersect. Tacsonia (subgenus Passiflora), in Peru - Caicedo-Baltodano, Miguel Antonio (2026)
Supersection Tacsonia (Passiflora L.) is a high-Andean lineage whose geographic restriction and environmental specialization make it particularly vulnerable to ongoing climate change. However, broad-scale evidence integrating distribution patterns, endemism, protection coverage, and future habitat stability remains limited for the Peruvian Andes. Here, we assessed the spatial distribution, richness patterns, habitat associations, and climate-driven vulnerability of Tacsonia species in Peru. We compiled 1,758 georeferenced occurrence records for 25 Tacsonia species (including one unidentified taxon) spanning elevations of 1,500–4,500 m and summarized richness across administrative regions, elevation bands, and latitudinal/longitudinal gradients. We also evaluated protection coverage by intersecting records with the national protected-area system and developed ecological niche models to estimate current suitability and potential losses under climate-change scenarios. Most records occurred between 3,000 and 3,500 m, and 23 species were found between 2,500 and 3,000 m. Cusco concentrated the highest number of observations (543) and species richness (14), followed by Cajamarca (226 records; 11 species). Richness peaks were detected around 6°, 7°, and 13°S and 72°, 75°, and 77°W. Thirteen species are endemic to the Peruvian Andes, including five restricted to Cusco, La Libertad, and Amazonas. Tacsonia species occupy multiple Andean ecosystems (Tropical Dry Forest, Páramo, Puna, Yungas, and Andean Dry Forest), with P. tripartita occurring across all habitat types. Occurrences were recorded within several protected areas (Alto Mayo, Pui Pui, Manu, Río Abiseo, Huascarán, Yanachaga-Chemillén, Calipuy, Cotahuasi, Pampa de Ayacucho, Machu Picchu, and Ampay), including endemic taxa such as P. amazonica, P. huamachucoensis, P. parvifolia, P. peduncularis, P. trifoliata, P. trisecta, and P. weigendii. Niche models indicated high current suitability along northern slopes and across the central and southern eastern Andes (AUC = 0.94), but projected climate change could reduce suitable habitat by ~20%–60% by 2100.